All-organic non-percolative dielectric composites with enhanced electromechanical actuating performances by controlling molecular interaction. Issue 124 (27th November 2015) - Yang, Dan; Huang, Shuo; Wu, Yibo; Ruan, Mengnan; Li, Shuxin; Shang, Yuwei; Cui, Xiuguo; Zhou, Jiaxin; Guo, Wenli; Zhang, Liqun
Abstract : An all-organic non-percolative dielectric elastomer with enhanced electromechanical actuating performances was fabricated by controlling molecular interaction. Abstract : Dielectric elastomers (DEs), which are capable of displaying considerable stress and strain in response to an applied electric field, have shown the closest similarity in performance to natural muscles. However, the high operating voltage of DEs limits their practical application. A reduction of the operating voltage can be achieved through increasing the dielectric constant and/or decreasing the elastic modulus. Here, an all-organic non-percolative dielectric composite with enhanced electromechanical actuating performance was prepared by introducing polyaniline (PANI) and epoxidized soybean oil (ESO) into a nitrile-butadiene rubber (NBR) matrix. A small amount of PANI was used to increase the dielectric constant through adding electron movement which is similar to dipole polarization, while ESO was used to decrease the elastic modulus of the composite through weakening intermolecular interactions in NBR and molecular interaction between NBR and PANI. Finally, an actuated strain of 2.5% was obtained at 4.5 V μm −1 by 4 phr PANI/NBR composite filled with 50 phr ESO, a 700% improvement in actuated strain compared with the actuated strain (0.31%) of pure NBR at 4.5 V μm −1 without any pre-strains. In comparison with other dielectric composites filled with conductive filler, the ESO/PANI/NBR composite also displays a relative advantage under conditions of no pre-strain and low electric field.